Potential of field grown sweet sultan (Centaurea moschata) as cut flower based on vase life - PERINBAN, SELLAM; SINGH, BABITA; RAI, PUJA; MAJUMDER, JAYOTI (The Indian Journal of Agricultural Sciences, 2016)
The present study was conducted to evaluate the vase life of sweet sultan (Centaurea moschata L.) in different vase solutions with view to use it as cut flower. Various vase solutions such as sucrose @ 2% and in combination with 8-hydroxyquinoline citrate (8-HQC) @ 200ppm, ethanol @ 2% and plant bio-regulators like aminooxy acetic acid (AOA) @ 0.5 mM, salicylic acid (SA) 150 ppm and benzyl adenine (BA) 50 mg/l, ascorbic acid (200 ppm) were used. Vase life of flowers was found as 4.67 days in control and 6.0 days in treatment with sucrose (2%) alone. However, the vase life was significantly increased in treatments with plant bio regulators namely ascorbic acid, salicylic acid, benzyl adenine and AOA (9.67, 9.33 days and 9 days/respectively). Treatments with 8 HQC and ethanol along with sugar also increased the vase life of the flowers significantly than control. Maximum increase in flower weight (7.80g) was observed in treatment with AOA on 8th day whereas, maximum flower diameter (71.80 mm) was observed in treatment with BA on 10th day. The maximum membrane stability index (57.50%) and total chlorophyll content of bract (1.22 mg/g) were recorded in treatment with ascorbic acid after 9 days of vase life.